Kritik Interpretasi Otoritatif: Studi Hermeneutika Khaled M. Abou El-Fadl - Hanik Rosyida (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2021)
Interpretation on the Qur’an has faced stagnation for using textual paradigm in exploring the meaning of the Qur’an. Since then, the developing social problems can’t find the solutions from the Qur’an, even those are forced to apply the meaning of the Qur’an interpreted in classical context. In contemporary era, there is shifting paradigm in interpretation, which is not merely focused on textual meaning, but has started to seek for textual meaning of the Qur’an by using hermeneutics. However, a number of theories on hermeneutics show their subjectivism in relation with the ideas developed by contemporary Muslim scholars. This comes from their distinguished social and intellectual conditions, especially their concern in looking at their surrounding condition. Most of scholars in hermeneutics offered new theories focused on method of interpretation. Here, Khaled M. Abou El Fadl, an exponent on hermeneutics, offered his hermeneutical thought in criticizing the concept of authority in interpreting the Qur’an. This study aims to explain the ideas of Khaled M. Abou El Fadl in Hermeneutics and Islamic Law, his social and intellectual context as the background of his idea.